2007
DOI: 10.1007/s12288-008-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

A study-screening of blood donors for blood transmissible diseases

Abstract: Aims Blood donors are of voluntary and replacement type. All donors, especially voluntary, are considered as `low risk' for seropositive status for Hepatitis B and C, HIV and syphilis. The present study endeavors to screen blood donors-a `low risk' group and evaluate the resultant data.Methodology We screened 23,068 donors serologically over 2 years for the above blood transmissible diseases. Serum alanine aminotranferase (ALT) and bilirubin were evaluated as surrogate markers in hepatitis B and C positive don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[7] More recently, a tertiary care hospital in Delhi reported that only 1% of healthcare workers were HBsAg-positive. [8] Other studies done in the various parts of India shows HBsAg prevalence of 1-1.7% in various studies, which is lower than the HBV carrier frequency of 2-4% in the general population. [9] This decreasing trend is most probably due to increasing awareness regarding these infections and hepatitis B vaccination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[7] More recently, a tertiary care hospital in Delhi reported that only 1% of healthcare workers were HBsAg-positive. [8] Other studies done in the various parts of India shows HBsAg prevalence of 1-1.7% in various studies, which is lower than the HBV carrier frequency of 2-4% in the general population. [9] This decreasing trend is most probably due to increasing awareness regarding these infections and hepatitis B vaccination.…”
Section: Discussionmentioning
confidence: 98%
“…Reports from India, [8,11] Pakistan, [3] Nepal, [2,12] Egypt, [13] Brazil, [14] and Nigeria [5] indicate that only 16-60% of HCW have received complete HBV immunization. In these countries, paramedics were more often unaware of HBV/HCV transmission and less often received HBV vaccination than doctors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] This article reviewed available literature from SSA, but many articles from Asia proved to suffer from the same shortcomings [ Table 2 ]. In articles published in the last 10 years on viral marker comparisons between VNRD and FRD in the Indian subcontinent, none carried out assay confirmation and only one examined the impact of age in epidemiologic data[ 34 35 36 37 38 39 40 41 42 43 ] and Table 2 . No studies account for the bias of repeat VNRDs in data analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, two of these articles did not find differences between the two types of donors. [ 36 40 ] The study stratifying for age found no difference between VNRD and FRD for HBsAg prevalence but significantly less in VNRD for anti-HCV though without confirmation. [ 42 ]…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the availability of the hepatitis B vaccine, numerous cross-sectional surveys showed that HCWs had a three to five-fold higher seroprevalence of HBV infection than the general U.S. population. (7,11,12,13,14) This decreasing trend is most probably due to increasing awareness regarding these infections and hepatitis B vaccination. Out of 37 doctors, 32 were fully vaccinated and only one was a non-responder, in nursing staff out of 18 none had taken HBV vaccination but 38.9 %(7) had protective antiHBs levels.…”
Section: Discussionmentioning
confidence: 99%